Nutrients in dairy and their implications for health and disease - Watson, Ronald Ross 1942-; Collier, Robert J.; Preedy, Victor R. (Academic Press, an imprint of Elsevier, 2017)
Nutrients in Dairy and Their Implications for Health and Disease addresses various dairy products and their impact on health. This comprehensive book is divided into three sections and presents a balanced overview of the health benefits of milk and milk products. Summaries capture the most salient points of each chapter, and the importance of milk and its products as functional foods is addressed throughout. Presents various dairy products and their impact on health Provides information on dairy milk as an important source of micro-and macronutrients that impact body functions Addresses dietary supplements and their incorporation into dairy products
Includes bibliographical references and index
Keywords: HEALTH & FITNESS / Healthy Living; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Preventive Medicine; Dairy products in human nutrition; Nährstoffgehalt; Gesundheit; Milchprodukt